RESOURCE ENDOWMENT, CONTINUOUS INNOVATION, AND THE COMPETITIVE ADVANTAGE OF ENTERPRISES IN LESS DEVELOPED AREAS: A CASE STUDY OF ERDOS GROUP - Eerdun Taoketao; Wang Yujie; Dong Ying; Wei Lisi; Zhao Yunhui (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
In recent years, the development of enterprises in less developed areas and how they gain and sustain a competitive advantage has become a popular issue among economists, managerialists, and sociologists. This paper first reviews and summarizes the literature on theories pertaining to resource endowment, continuous innovation, and enterprises’ competitive advantage. It then constructs a theoretical model of resource endowment, technological innovation, and enterprise competitive advantage in less developed areas. Using Erdos group as a case study, we conducted a field survey and in-depth interviews in order to analyze the source of its competitive advantage.